Estimate of the Best Constant of Discrete Hardy-Type Inequality with Matrix Operator Satisfying the Oinarov Condition - Kalybay, Aigerim; Shalginbayeva, Saltanat (Eurasian Mathematical Journal, 2024)
This paper studies the weighted inequality of Hardy-type in discrete form for matrix operators satisfying the Oinarov condition. Necessary and sufficient conditions on the weight sequences under which the Hardy-type inequality holds were found in various studies. In this paper, we extend the result with a two-sided estimate of the inequality constant.